INFUSA DAUN JAMBU BIJI ( Psidium guajava L.) SEBAGAI BAHAN ANTIMIKROBA PADA RONGGA MULUT - siti nur yani (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2017)
Abstract Background: Guava plants (Psidium guajava Linn) are found throughout Indonesia. The leaves contain tannins that can be exploited as antibacterial and antifungal. The presence of fungi and bacteria in the oral cavity can be a problem in oral and dental health.The purpose of this research is to know the infusa of guava leaf 10%, 20% to decrease the number of oral germs as wellMethods: The experimental study used 30 primary school children divided into 3 groups. Group 1 was taken saliva sample before and after gargle with 10% guava leaf infusa. Group 2 was taken saliva sample before and after rinsing with 20% guava leaf infusion, and for group 3 with brand X mouthwash. Saliva samples taken before and after rinsing with all three ingredients were then examined using the Total Plate Count method.The results showed that the numbers of germs before and after rinsing with 10% and 20% casque seed infections were significantly different (sig 0.001 and 0.000). The average difference between the 10% infusa and the X brand drug shows an un-coercive difference (sig 0.947).Conclusion Guava leaves infution 10% and 20% can decrease the number of oral germs. Both concentrations of guava leaf infution compared with X brand mouthwash have no significant difference in reducing germ numbers. Keywords: guava leaf infution, number of germs, oral cavity